Comparison of false-negative/positive results of intraoperative evoked potential monitoring between no and partial neuromuscular blockade in patients receiving propofol/remifentanil-based anesthesia during cerebral aneurysm clipping surgery: A retrospective analysis of 685 patients. Issue 34 (August 2016) - Kim, Sung-Hoon; Jin, Seok-Joon; Karm, Myong-Hwan; Moon, Young-Jin; Jeong, Hye-Won; Kim, Jae-Won; Ha, Seung-Il; Kim, Joung-Uk
Abstract : Abstract: Although the elicited responses of motor evoked potential (MEP) monitoring are very sensitive to suppression by anesthetic agents and muscle relaxants, the use of neuromuscular blockade (NMB) during MEP monitoring is still controversial because of serious safety concerns and diagnostic accuracy. Here, we evaluated the incidence of unacceptable movement and compared false-negative MEP results between no and partial NMB during cerebral aneurysm clipping surgery. We reviewed patient medical records for demographic data, anesthesia regimen, neurophysiology event logs, MEP results, and clinical outcomes. Patients were divided into 2 groups according to the intraoperative use of NMB: no NMB group (n = 276) and partial NMB group (n = 409). We compared the diagnostic accuracy of MEP results to predict postoperative outcomes between both groups. Additionally, we evaluated unwanted patient movement during MEP monitoring in both groups. Of the 685 patients, 622 (90.8%) manifested no intraoperative changes in MEP and no postoperative motor deficits. Twenty patients showed postoperative neurologic deficits despite preserved intraoperative MEP. False-positive MEP results were 3.6% in the no NMB group and 3.9% in the partial NMB group ( P  = 1.00). False-negative MEP results were 1.1% in the no NMB group and 4.2% in the partial NMB group ( P  = 0.02). No spontaneous movement or spontaneous respiration was observed in either group. Propofol/remifentanil-based anesthesia without NMB decreases the stimulation intensity of MEPs, which may reduce the false-negative ratio of MEP monitoring during cerebral aneurysm surgery. Our anesthetic protocol enabled reliable intraoperative MEP recording and patient immobilization during cerebral aneurysm clipping surgery.